Faktor-Faktor yang Mempengaruhi Rencana Pemekaran Wilayah Kecamatan di Kota Tanjungpinang - Mandala, Edward; Erria Khairunnisa, Rafifah; A. Karim, Zamzami; Setyadiharja, Rendra; Mukhlis, Suhardi (STISIPOL Raja Haji, 2024)
Based on the results of the 2010 Tanjungpinang City Subdistrict Expansion Study, it appears that the results of the study recommend that the Tanjungpinang City area be divided into 7 subdistricts, of which 3 subdistricts are new subdistricts that must be expanded. However, in real conditions up to now in 2020, the existing sub-district conditions in Tanjungpinang City still consist of 4 (four) sub-districts and have not yet realized the second recommendation of the sub-district expansion study. The purpose of this research is to determine the factors that influence the plan to expand sub-district areas in Tanjungpinang City. This research method is descriptive qualitative. Where data will be collected using observation techniques, interviews and documentation studies. The data analysis technique in this research is qualitative analysis. The informants in this research were all Regional Apparatus Organizations related to the expansion of sub-district areas, the DPRD Secretariat of Riau Islands Province, the Regional Government and Autonomy Bureau of the Regional Secretariat of Riau Islands Province, the Regional Secretariat of Tanjungpinang City, the sub-district heads of Tanjungpinang City. The results of this research are that the factors that influence the plan for the expansion of sub-district areas in Tanjungpinang City are: Economic Capability Factors, Regional Potential, Socio-Cultural and Population, Social Politics, Area Size, Defense and Security, Span of Control for Government Administration, One suggestion What can be given is that the Tanjungpinang City Government should pay special attention to the economic potential of an area that will be expanded.